Rizal (His life, works, writings) & the other heroes : the freehand modular approach - De Jesus, Maria Bernadette Austria (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2017)
It with the comprehensive and concise relevant facts of the life, works and writings of Rizal, it was written with the rationale of making students and reader's conscious of Rizal's noble sacrifice and exemplary ideals.
Module 1 : Republic Act 1425, NHI Hero -- Module 2 : The 19th Century world of Rizal and the Dawn of Nationalism -- Module 3. Backgrounder of Rizal's family -- Module 4 : Rizal's Birth, childhood and formal Schooling -- Module 5 : Rizal's travels and aspirations -- Module 6 : Rizal's exile, Trial, execution and Martyrdom -- Module 7 : The Many faces of Rizal -- Module 8 : Jose Rizal's writings -- Module 9 : Jose Rizal's works -- Module 10 : Reappraisal of some Issues -- Module 11 : The hero in you
Includes bibliographical references.
Keywords: RIZAL, JOSE P